?Reduction In Post-Harvest Losses of Winter and Summer Crops of Guava: Short Communications (Biological Sciences - PJSIR, 1995)
Guava (Psidium guajava) is a perishable commodity andhas a very short shelf-life at ambient temperature. Extensionin shelf-life of fruits by reducing enzymic activity,